Geochemistry and statistical analyses of porphyry system and epithermal veins at Hizehjan in northwestern Iran - Radmard, Kaikhosrov; Zamanian, Hassan; Hosseinzadeh, Mohamad Reza; Khalaji, Ahmad Ahmadi (Geologos, 2017)
Situated about 130 km northeast of Tabriz (northwest Iran), the Mazra’eh Shadi deposit is in the Arasbaran metallogenic belt (AAB). Intrusion of subvolcanic rocks, such as quartz monzodiorite-diorite porphyry, into Eocene volcanic and volcano-sedimentary units led to mineralisation and alteration. Mineralisation can be subdivided into a porphyry system and Au-bearing quartz veins within andesite and trachyandesite which is controlled by fault distribution. Rock samples from quartz veins show maximum values of Au (17100 ppb), Pb (21100 ppm), Ag (9.43ppm), Cu (611ppm) and Zn (333 ppm). Au is strongly correlated with Ag, Zn and Pb. In the Au-bearing quartz veins, factor group 1 indicates a strong correlation between Au, Pb, Ag, Zn and W. Factor group 2 indicates a correlation between Cu, Te, Sb and Zn, while factor group 3 comprises Mo and As. Based on Spearman correlation coefficients, Sb and Te can be very good indicator minerals for Au, Ag and Pb epithermal mineralisation in the study area. The zoning pattern shows clearly that base metals, such as Cu, Pb, Zn and Mo, occur at the deepest levels, whereas Au and Ag are found at higher elevations than base metals in boreholes in northern Mazra’eh Shadi. This observation contrasts with the typical zoning pattern caused by boiling in epithermal veins. At Mazra’eh Shadi, quartz veins containing co-existing liquid-rich and vapour-rich inclusions, as strong evidence of boiling during hydrothermal evolution, have relatively high Au grades (up to 813 ppb). In the quartz veins, Au is strongly correlated with Ag, and these elements are in the same group with Fe and S. Mineralisation of Au and Ag is a result of pyrite precipitation, boiling of hydrothermal fluids and a pH decrease.